Meta-Analysis of the Therapeutic Effect of Shenqi Jiangtang Granule on Type 2 Diabetes Mellitus. (29th September 2020) - Li, Ruo-Lan; Dong, Tai-Wei; Wei, Ji-Gang; Gao, Feng; Li, Min; Bai, Yang; Wei, Pei-Feng; Xi, Miao-Miao
Abstract : Objective . To systematically evaluate the effectiveness of Shenqi Jiangtang granule (SQJT) in the treatment of type 2 diabetes. Methods . We searched CNKI, Wanfang Data, VIP, and PubMed databases to collect randomized controlled trials (RCT) of Shenqi Jiangtang granules in the treatment of type 2 diabetes. The search time was from January 2014 to the present. Data were extracted, and quality was evaluated. Metadata analysis of the extracted data was carried out using RevMa5.2 software. The final results are expressed in relative risk (RR), mean difference (MD), and 95% CI. Results . This study included a total of 13 studies, 1160 subjects. Meta-analysis results showed that the test group was better than the control group (RR = 1.26, 95% CI 1.18–1.34, P < 0.00001 ). The fasting blood glucose, postprandial blood glucose, and glycated hemoglobin of the test group were also significantly better than those of the control group. Conclusion . Shenqi Jiangtang granules have a certain clinical effect and low adverse reaction rate for the treatment or adjuvant treatment of type 2 diabetes. At present, the drug has been widely used in clinical practice, but a large number of large-sample clinical trials are needed to further verify its specific efficacy and safety.